(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
School is a place for children to get formal education. In addition to a place of learning, schools are also a place that can be a threat to disease transmission. Deaths due to diarrhea are up to 65%, and other diseases are 26%. clean and healthy living behavior is an effort to provide learning experiences or create a condition for individuals, families, groups, and communities by providing communication channels, delivering information, and conducting education to improve knowledge, attitudes, and behavior. This community service aimed to provide knowledge and understanding of clean and healthy living behavior to elementary school children so that they can practice it in their daily lives. This community service was conducted by providing counseling using lecture methods, question-and-answer discussions, and simulation using LCD media and props. The activity ran well, and all participants were enthusiastic about this service activity.